AKULTURASI ISLAM DAN BUDAYA LOKAL: STUDI ATAS TRADISI KEAGAMAAN MASYARAKAT JAWA TIMUR - Rofi'atul laili; Ahmad Halid (TASHWIR, 2025)
Abstract: The phenomenon of cultural acculturation is the result of interactions between different cultures within a single geographical area. In the Tapal Kuda region of East Java, the community demonstrates a unique blend of Madurese and Javanese cultures, particularly in religious practices. This study aims to examine the forms of acculturation between Islam and local culture, the dynamics of the relationship between Madurese and Javanese traditions, and the types of syncretism that have developed within East Javanese society. This research employs a descriptive qualitative approach through participatory observation, in-depth interviews, and literature review. The findings indicate that cultural and religious acculturation in East Java occurs dynamically and harmoniously, enriching Islamic expression without diminishing the essence of religious teachings. Keywords: Acculturation, Islam and Local Culture, East Java, Religious Traditions